Pengaruh Perceived Price, Social Influence dan Hedonic Motivation Terhadap Sikap serta Dampaknya Terhadap Minat Pembelian - Muhammad Indrawan Sulaksono; Triyono Arief Wahyudi (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
Business in Creative Industry is growing rapidly. One of them is focus on the fashion sub-sector. Many Creative Industry entrepreneurs combine fashion with some driving communities. The Good Condition is a brand that offers gloves for motorcycle riders with many choice of colors and models. However, in business development, sometimes there are many obstacles to face by the owner, that makes customer’s purchase intention decreases, especially in this pandemic Covid 19 situation. Therefore, the researcher analyzes the effect of perceived price, social influence, and hedonic motivation on customer’s purchase intention with attitudes as the mediating variable. The research used was quantitative by distributing questionnaires to 180 Good Condition’s customers. The research results indicate that perceived price, social influence, and hedonic motivation have a positive and significant effect on customer’s attitudes and have an impact on customer’s purchase intention.